2018
DOI: 10.1002/cbin.11036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlation of apoptosis in human granulosa cells—A review

Abstract: The quality of oocytes depends on interactions with surrounding granulosa cells. Granulosa cells are essential in normal follicular maturation process since they produce steroidal hormones and growth factors, and they play a crucial role in follicular atresia. The success in reproductive biology and medicine depends on reliable assessment of oocyte and embryo viability which presently mainly bases on oocyte and embryo morphology. Recent investigations have tried to establish an evaluation system for oocyte qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Granulosa cells (GCs) being one type of the important somatic cells of ovarian follicles play a key role in the growth and development of the follicles. GCs secrete steroid hormones and provide nutritional support for oocyte development [8][9][10] Studies have shown that apoptosis occurred in 10% or more of GCs population will cause follicle atresia, which results in reproductive disorders [11][12][13] ZEA is shown to cause ovarian GCs apoptosis as well as steroid hormone secretion disorders and reproductive disorders 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Granulosa cells (GCs) being one type of the important somatic cells of ovarian follicles play a key role in the growth and development of the follicles. GCs secrete steroid hormones and provide nutritional support for oocyte development [8][9][10] Studies have shown that apoptosis occurred in 10% or more of GCs population will cause follicle atresia, which results in reproductive disorders [11][12][13] ZEA is shown to cause ovarian GCs apoptosis as well as steroid hormone secretion disorders and reproductive disorders 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The cumulus granulosa cells envelop the oocyte and have cross-talk with the oocyte across the zona pellucida, while the mural granulosa cells are separated from the oocyte by the cumulus cells and by the antral cavity filled with follicular fluid. Both the mural granulosa cells and the cumulus cells produce and secrete steroidal hormones as well as growth factors into the follicular fluid [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although apoptosis occurs as a physiological process in the ovary, being highly important throughout the phases of follicular development, apoptosis in dominant follicles may interfere in ovulation and oocyte quality [25]. Therefore, excessive apoptosis of GCs definitely has negative effects on ovarian function during perimenopause symptoms [8]. Our current findings indicated that PFC considerably reduced apoptosis of GCs in the ovary of aging mice, which could be the molecular basis for PFC improvement of ovarian histology and function.…”
Section: Discussionmentioning
confidence: 62%
“…The major functions of GCs include the production of sex steroids, as well as myriad growth factors thought to interact with the oocyte during its development [7]. Emerging evidence suggests that apoptosis of GCs is concomitant with aging-associated ovarian function decline leading to ovarian hormone secretion disorder [8]. Therefore, prevention of GCs apoptosis represents a novel strategy for treatment of perimenopause symptoms.…”
Section: Introductionmentioning
confidence: 99%